PENGARUH KECUKUPAN MODAL (CAR), EFISIENSI OPERASIONAL (BOPO), DAN KUALITAS PEMBIAYAAN (NPF) TERHADAP PROFITABILITAS (ROA) PADA BANK SYARIAH DI INDONESIA - Suhadi, Suhadi; Inaroh, Dewi (MALIA: Journal of Islamic Banking and Finance, 2017)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), and Financing Quality (NPF), to Profitability (ROA) at Bank Syariah period 2009-2013. The sample in this research is quarterly financial report of 3 Bank Syariah (BRI Syariah,Bank Mandiri Syariah, and Bank Mega Syariah) period 2009-2013. Data analysis used classical assumption test. The result of the research shows that Operational Efficiency (BOPO) has significant effect to Profitability (ROA) with significance level of 0. 000% and tcount of 6, 900. While Capital Adequacy (CAR) and Financing Quality (NPF) did not affect the level of profitability (ROA) with the level of significance of each of 0.322% and 0.666% and t arithmetic respectively of 1,000 and 0. 435. While F test get F count equal to 20, 053 with significance level equal to 0. 000%, this indicates that Capital Adequacy Level (CAR), Operational Efficiency (BOPO), and Financing Quality (NPF), influence to Profitability (ROA). Combined independent variables of this study can explain the variability level of profitability(ROA)of Islamic banks by 49.2%.Keywords: capital,efficiency,profitability